Pola Penggunaan Antibiotik Pada Pasien Pneumonia Dewasa Rawat Inap RSU PKU Muhammadiyah Bantul Periode Tahun 2022 - Mithasari Hutami; Hanita Christiandari; Jarot Yogi Hernawan (An-Najat, 2024)
The prevalence of pneumoniae deaths in the world is around 2.56 million people in 2017. Based on the 2018 Riskesdas data, in Indonesia there has been an increase in the prevalence of pneumonia at all ages from 1.6% (2013) to 2.0% (2018). Pneumonia is an inflammation of the lungs that causes pain when breathing and limits oxygen intake. Pneumonia is caused by bacteria, viruses or mycoplasma. Antibiotics are the main drug in the management of infectious diseases. Adult patients are the groups most at risk for pneumoniae. Purpose: Knowing the pattern of antibiotic use in hospitalized adult pneumonia patients at RSU PKU Muhammadiyah Bantul for the 2022 period. This research is a non-experimental descriptive study. The sample used was 170 patients. Recording of patient data includes the patient's RM number, gender, age, drug given. Data were processed and analyzed descriptively, then calculated in percentage form and presented in tabular form. Results the research it showed the results of patients with an inpatient diagnosis of pneumonia dominated by men 59% and the elderly group 65%. The most widely used class of antibiotics were cephalosporin 36.65%, macrolide 33.22% and quinolones 22.95%. The most widely used antibiotic names were azithromycin 33.22%, ceftriaxone 23.63%, and levofloxacin 19.18%. The most common route of administration of antibiotics was the parenteral route 83% and the oral route 17% with the longest duration of administration of antibiotics for 3 days 47%, 5 days 36%, 7 days 12%, and 5% for administration of antibiotics > 7 days. Conclusion: Patients diagnosed with adult pneumoniae were dominated by 59% of men and 65% of the elderly group. The most widely used class of antibiotics was cephalosporins at 36.65%. The most widely used parenteral antibiotic was azithromycin at 33.22% with the longest duration of antibiotics being 3 days at 47%.